Sustainability Reporting By Universities In Indonesia Abstract - Birowo Yasbie; Zuni Barokah (The Indonesian Journal of Accounting Research, 2018)
Abstract: This study aims to describe sustainability reporting practices by universities in Indonesia by knowing the reporting channel used by universities and the conformity of information disclosure with GRI G4 indicator and campus sustainability assessment instrument. This study uses a framework with 73 indicators based on GRI and a campus sustainability assessment instrument to analyze information disclosed by universities in Indonesia. The results of the analysis show that the level of disclosure of sustainability information conducted by universities in Indonesia is lower when compared with universities in Canada and Lithuania. Disclosure of information undertaken by universities in Indonesia remains limited in scope, and no universities disclose sustainability information in an integrated report. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan praktik pelaporan keberlanjutan oleh perguruan tinggi di Indonesia dengan mengetahui saluran pelaporan yang digunakan oleh universitas dan kesesuaian pengungkapan informasi dengan indikator GRI G4 dan instrumen penilaian keberlanjutan kampus. Penelitian ini menggunakan kerangka kerja dengan 73 indikator berdasarkan GRI dan instrumen penilaian keberlanjutan kampus untuk menganalisis informasi yang diungkapkan oleh universitas di Indonesia. Hasil analisis menunjukkan bahwa tingkat pengungkapan informasi keberlanjutan yang dilakukan oleh universitas di Indonesia lebih rendah bila dibandingkan dengan universitas di Kanada dan Lithuania. Keterbukaan informasi yang dilakukan oleh universitas di Indonesia masih terbatas dalam ruang lingkupnya, dan tidak ada universitas yang mengungkapkan informasi keberlanjutan dalam laporan terpadu.